An integrative process of blast furnace and SOEC for hydrogen utilization: Techno-economic and environmental impact assessment. (15th December 2021) - Kim, Jinsu; Lee, Hyunjun; Lee, Boreum; Kim, Jungil; Oh, Hyunmin; Lee, In-Beum; Yoon, Young-Seek; Lim, Hankwon
Highlights: H2 injection in the blast furnace is simulated by Rist operating diagram. Economics and CO2 emission impacts of the renewable SOEC process are discussed. The economic parity reaches at 2036 ∼ 2045 depending on the SOEC process maturity. The annual CO2 emission reduction potential was estimated to be 1.16 MtCO2-eq. Abstract: The steel sector is one of the most carbon-intensive industries, and the sustainable strategies to reduce CO2 emission on integrated mill plants are discussed continuously. By renewable H2 utilization on blast furnace (BF), it is expected to achieve both sustainable operation and CO2 emission reduction. We evaluate the application of the solid oxide electrolysis cell (SOEC) process as a source of H2 for use as an alternative to CO as the reductant in a BF. We mathematically formulated a BF model and developed an integrated BF-SOEC process. We performed techno-economic analysis to suggest the maximum H2 injection for the technical aspect, and demonstrated the process' economic viability, considering the learning-by-doing effects on the price of the SOEC system. We also estimated the net reduction of global warming potentials and carbon intensity. Our findings showed that the coke replacement ratio ranged from 0.255 ∼ 0.334 k g C o k e ∙ k g H 2 - 1 depending on injection conditions and that 25 k g H 2 ∙ t H M - 1 was an acceptable maximum injection rate within the stable range of BF operating indexes. We calculated H2 production cost to be US 8.84 ∼ 8.88 k g H 2 - 1 in the present, but it is expected to be decreased to US 1.41 ∼ 4.04 k g H 2 - 1 by 2050. Economic parity with the existing BF process will be reached between the years 2036 and 2045, depending on the maturity of the SOEC process. Injection of 25 k g H 2 ∙ t H M - 1 can reduce CO2 emission by 0.26 ∼ 0.32 t C O 2 - e q . ∙ t H M - 1 We expect that this sustainable strategy to reduce CO2 emission from integrated mill plants will widen applications of H2 utilization in BFs if the economic efficiency of SOEC systems can be increased.